Studying Gender Gap In Terms Of Work, Education And Health In The Northern And North-Eastern Region In Syria - Issa, Haitham Ahmad; Sultan, Thaer Jamail (Latakia University Journal - Economic and Legal Sciences Series, 2019)
This paper tries to explore the gender gap in the Northern and North-Eastern area in Syria from three key pillars i.e. work, education and health, using the database of the fast population survey undertaken by the Commission for Planning and International Cooperation and UNFPA in Syria. In details, the study aims to conduct an in-depth analysis of the opinions and attitudes of individuals from different social groups in the subject areas that represent the dimensions of the gender gap. The work dimension focused the reasons of accepting women’s work as well as studying the reasons for refusing that work to identify enabling and hindering factors of that work. In addition, some related issues that might be affected by woman work were studied such as men participation in household work, woman role in formulating household decisions and her right to inheritance. In the education dimension, the study focused on exploring parents’ preferences towards the education level for their children and the effects of that preferences on children attainment and study. The health dimension examined some behaviors and have different health implications between men and women such as the preferred age at first marriage, the preferred age to stop giveng birth and early pregnancy etc. The study concludes with some results of which: (1) there is a gender gap with regard to accepting work outside family home, (2) there is noticeable difference in the education level that parents prefer for their boy and that for their daughters, (3) there are widespread of some behaviors and practices that have adverse effects on women’s health. يسعى البحث إلى سبر فجوة النوع الاجتماعي في المنطقة الشمالية والشمالية الشرقية في سورية من ثلاثة محاور أساسية هي العمل والتعليم والصحة باستخدام قاعدة بيانات المسح السكاني السريع الذي قامت به هيئة التخطيط والتعاون الدولي مع صندوق الأمم المتحدة للسكان في سورية. بالتفصيل، هدف الدراسة هو إجراء تحليلٍ موسعٍ لآراء ومواقف الأفراد من مختلف الفئات الاجتماعية في المنطقة المدروسة في مواضيع محاور البحث الثلاثة التي تُمثل أبرز أبعاد قضية النوع الاجتماعي. ركّز محور العمل على أسباب قبول عمل المرأة خارج المنزل بالتوازي مع دراسة أسباب عدم الموافقة عليه للتعرّف على العوامل المساعدة لعملها والمعيقة له؛ بالإضافة إلى دراسة مسائل قد يؤثر فيها عمل المرأة مثل مشاركة الرجل في الأعمال المنزلية ودور المرأة في صياغة قرار الأسرة وحقها في الإرث. في محور التعليم، ركّزت الدراسة على سبر تفضيلات الأهل للمستوى التعليمي المُفضل لأبنائهم وبناتهم وانعكاس تلك التفضيلات على انتظام الأبناء والبنات فعلياً في الدراسة. في محور الصحة، تمّ التركيز على بعض السلوكيات والممارسات التي تؤثر في الصحة بشكلٍ متباين بين الذكور والإناث مثل العمر المرغوب عند الزواج الأول والعمر المرغوب للتوقف عن الإنجاب والحمل المبكر وغيرها. توصلت الدراسة إلى عدة نتائج منها (1) وجود فجوة بين الرجل والمرأة في مجال قبول العمل خارج المنزل، (2) وجود فارق واضح في المستوى التعليمي الذي يرغبه الأهل لأبنائهم وبناتهم لصالح المجموعة الأولى، و(3) شيوع العديد من الممارسات والسلوكيات ذات الأثر السلبي في المستوى الصحي عند الإناث مقارنة بالذكور كتفضيل الزواج المبكر والحمل المبكر للإناث واستمرارهن في الإنجاب وعدم المعرفة بأهمية الفحص الطبي قبل الزواج وغيره.